Computational investigation of intrinsic localization in crystalline Si - Voulgarakis, Nikolaos K.; Hadjisavvas, George C.; Kelires, Pantelis C. (My University, 2004)
We investigate numerically existence and dynamical properties of intrinsic localization in crystalline silicon through the use of interatomic Tersoff force fields. We find a band of intrinsic localized modes (discrete breathers) each with lifetime of at least 60 ps in the spectral region 548-578 cm -1, located just above the zone end phonon frequency calculated at 536 cm-1. The localized modes extend to more than second neighbors and involve pair central-atom compressions in the range from 6.1% to 8.6% of the covalent bond length per atom. Finite temperature simulations show that they remain robust to room temperatures or higher with a typical lifetime equal to 6 ps.
Keywords: Silicon; Mathematical analysis; Phonons